A Reflexive Thematic Analysis of Sufi-Informed Islamic Family Counseling for Conflict Resolution - Ishlakhatus Sa'idah; Bambang Dibyo Wiyono; Budi Purwoko (KONSELOR, 2026)
Recent research in Islamic counselling and psychology has explored spiritual strategies for family conflicts, but the experiential meaning of Sufi-based practices within counselling remains underexplored. Most existing studies describe Sufi ideas theoretically but rarely examine how counsellors and families experience these principles in tension, reconciliation, and relational adjustments. This study fills that gap by examining how specific Sufi values are embodied, interpreted, and applied in Islamic family counselling sessions. Using a hermeneutic-phenomenological approach inspired by van Manen, the research involved five Muslim counsellors and eight families, selected through purposive sampling from a community counselling network. Data collection included detailed interviews and ethically approved observations of counselling sessions during non-private moments. Analyses combined meaning-unit condensation with reflexive thematic analysis. Three experiential themes emerged: (1) inner readiness as an ethical foundation, where both counsellors and parents describe quieting the heart as essential for dialogue; (2) embodied spiritual regulation, with practices like dhikr helping to recalibrate emotional intensity and foster empathetic listening; and (3) relational deliberation, where Qur’an-guided reflection promotes more collaborative and less adversarial decision-making. These results offer a contextual understanding of how Sufi-inspired spirituality influences conflict resolution in Indonesian Muslim families. Further studies should explore these patterns in various settings and larger samples.